A next generation targeted amplicon sequencing method to screen for insecticide resistance mutations in Aedes aegypti populations reveals a rdl mutation in mosquitoes from Cabo Verde - Emma L. Collins; Jody E. Phelan; Magdalena Hubner; Anton Spadar; Monica Campos; Daniel Ward; Holly Acford-Palmer; Ana Rita Gomes; Keily Silva; Lara Ferrero Gomez; Taane G. Clark; Susana Campino (Public Library of Science (PLoS), 2022)
Aedes mosquito vectors transmit many viruses of global health concern, including dengue, chikungunya and Zika. These vector-borne viral diseases have a limited number of treatment options, and vaccines vary in their effectiveness. Consequently, integrated vector management is a primary strategy for disease control. However, the increasing emergence and spread of insecticide resistance is threatening the efficacy of vector control methods. Identifying mutations associated with resistance in vector populations is important to monitor the occurrence and evolution of insecticide resistance and inform control strategies. Rapid and cost-effective genome sequencing approaches are urgently needed. Here we present an adaptable targeted amplicon approach for cost-effective implementation within next generation sequencing platforms. This approach can identify single nucleotide polymorphisms (SNPs) and small insertions and deletions (indels) in genes involved in insecticide resistance in Aedes aegypti mosquitoes. We designed and tested eleven amplicons, which included segments of the ace-1 (carbamate target), the Voltage-Gated Sodium Channel (vgsc; pyrethroids, DDT and organochlorines), and rdl (dieldrin) genes; thereby covering established knockdown resistance (kdr) mutations (e.g., S989P, I1011M/V, V1016G/I and F1534C), with the potential to identify novel ones. The amplicon assays were designed with internal barcodes, to facilitate multiplexing of large numbers of mosquitoes at low cost, and were sequenced using an Illumina platform. Our approach was evaluated on 152 Ae. aegypti mosquitoes collected in Cabo Verde, an archipelago with a history of arbovirus outbreaks. The amplicon sequence data revealed 146 SNPs, including four non-synonymous polymorphisms in the vgsc gene, one in ace-1 and the 296S rdl mutation previously associated with resistance to organochlorines. The 296S rdl mutation was identified in 98% of mosquitoes screened, consistent with the past use of an organochlorine compound (e.g., DDT). Overall, our work shows that targeted amplicon sequencing is a rapid, robust, and cost-effective tool that can be used to perform high throughput monitoring of insecticide resistance. Author summary Many viruses, such as dengue and Zika, are transmitted by Aedes aegypti mosquitoes. These vector-borne diseases are a major public health problem in the tropics and sub-tropics worldwide. The primary strategy to reduce their burden is vector control, including through the application of insecticides. However, many mosquito populations have developed resistance to insecticides. Here, we present a rapid, robust, and cost-effective tool that allows the screening of genes associated with insecticide resistance across many Aedes aegypti mosquitoes, identifying known resistance and novel mutations. This assay will support vector control strategies by informing on the emergence and spread of insecticide resistance mutations across Aedes aegypti populations.